Male fertility and type 2 diabetes mellitus: effect of white tea - Tomás, Gonçalo David Cabral (2013)
Diabetes mellitus (DM) is one of the major public health problems and its increase incidence is closely related with a decrease in birth rates. Male infertility related with type 2 DM (T2DM) has been linked to reactive oxygen species (ROS) overproduction and increased testicular oxidative stress (OS). Tea is one of the most widely consumed beverages and its antihyperglycemic and antioxidant potential has been reported. Herein, we hypothesized that White Tea (WTEA) consumption by T2DM rats could prevent testicular OS preserving sperm quality. For that purpose, we used a neonatal STZ-induced diabetic rat model. At one month of age, water was substituted by WTEA during two months and testicular antioxidant potential and OS were evaluated, as well as sperm parameters in normal and T2DM rats drinking water or WTEA. WTEA consumption improved glucose tolerance and insulin sensitivity in T2DM rats. WTEA consumption restored protein oxidation and lipid peroxidation to normal levels. Testicular antioxidant potential was increased by WTEA consumption in T2DM, while testicular OS was decreased. Nevertheless, glutathione content and redox state was not altered. After WTEA consumption by T2DM rats, sperm concentration was improved while sperm motility, viability and the abnormal spermatozoa reached normal values evidencing that epididymal sperm quality was restored. Overall, our results show that WTEA consumption causes an important improvement in sperm parameters and thus in male T2DM reproductive function, due to a significant decrease in testes ROS production. WTEA consumption can be a natural, economical and good strategy to counteract the deleterious effects of T2DM in male reproductive function.